2020
DOI: 10.1186/s13065-020-00674-6
|View full text |Cite
|
Sign up to set email alerts
|

PCN-222 metal–organic framework: a selective and highly efficient sorbent for the extraction of aspartame from gum, juice, and diet soft drink before its spectrophotometric determination

Abstract: In this paper, we describe synthesis and application of an iron porphyrinc metal-organic framework PCN-222(Fe) for solid phase extraction of aspartame, an artificial non-saccharine sweetener, from gum, juice and diet soft drink samples prior to its determination by spectrophotometry. The mesoporous MOF was synthesized solvo-thermally and characterized by Fourier transform-infrared spectroscopy, powder X-ray diffraction, scanning electron microscopy, and Brunauer-Emmett-Teller techniques. To obtain the best ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…1.2 and 3 nm, corresponding to trigonal and hexagonal channels, respectively. 53 However, it is worth mentioning that variation of the reaction conditions for the synthesis, such as the amount and nature of the acid, results in different tunable pore sizes. 50 We used the Horvath−Kawazoe method considering spherical pores to obtain differential pore volume plots (Figure 1, insets).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.2 and 3 nm, corresponding to trigonal and hexagonal channels, respectively. 53 However, it is worth mentioning that variation of the reaction conditions for the synthesis, such as the amount and nature of the acid, results in different tunable pore sizes. 50 We used the Horvath−Kawazoe method considering spherical pores to obtain differential pore volume plots (Figure 1, insets).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous simulations and experimental results have shown that PCN-222 has two types of pores, with sizes of ca. 1.2 and 3 nm, corresponding to trigonal and hexagonal channels, respectively . However, it is worth mentioning that variation of the reaction conditions for the synthesis, such as the amount and nature of the acid, results in different tunable pore sizes .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above-mentioned discussion, a porous zirconium–porphyrin MOF with the formulation [Zr 6 (μ 3 -OH) 8 (OH) 8 (H 2 TCPP) 2 ] (PCN-222) was selected as an electrode material. PCN-222 has been widely studied in application fields such as catalysis, adsorption and separation, drug delivery, and chemical sensing ,, due to its excellent structure and properties. PCN-222 has both photoelectric activity and chemical binding property, and we constructed it as an ultrasensitive PEC probe for phosphate detection.…”
Section: Introductionmentioning
confidence: 99%
“…The full band assignment for TCCP(H 2 ), TCPP(Pd), PCN-222(H 2 ) and PCN-222(Pd) can be found in Table S2. 11 However, it is worth to mention that modulating different parameters during the syntheses, such as the amount and nature of acids, results in different tunable pore sizes. 12 We used the Horvath-Kawazoe method considering spherical pores to obtain the differential pore volume plots.…”
Section: Ultraviolet-visible (Uv-vis) Spectroscopymentioning
confidence: 99%